A novel nonsense variant in PLS3 causes X‐linked osteoporosis in a Chinese family. (26th July 2019) - Wang, Lianqing; Bian, Xinchao; Cheng, Guangying; Zhao, Peiqing; Xiang, Xinxin; Tian, Wenxiu; Li, Tao; Zhai, Qiaoli
Abstract: Osteoporosis is a complex bone metabolic disorder. Genetic factors play an important role in the development of osteoporosis. Mutations in more than 15 genes have been identified to be responsible for osteoporosis to date. Most recently, the gene PLS3 encoding plastin 3 was recognized to be involved in X‐linked osteoporosis. Here, we recruited a four‐generation Chinese family with X‐linked osteoporosis, which had its onset in childhood and was characterized by peripheral fractures and low bone mineral density. All affected individuals shared a nonsense variant (c.244C > T) in exon 4 of PLS3 on Xq23. The variant in affected individuals segregated with the osteoporosis phenotype. By restriction analysis using Dra I, this variant was confirmed in all affected individuals but was not detected in unaffected family members or in 100 unrelated Chinese male controls. The variant was predicted to cause a premature termination of messenger RNA (mRNA) translation (p.Gln82*). The mutant mRNA degraded via the mechanism of "nonsense‐mediated mRNA decay." In the present study, we identified a novel nonsense variant of PLS3 in early‐onset X‐linked osteoporosis and provided a novel insight into the molecular mechanism underlying the pathogenesis of osteoporosis.